Modelling of optical waveguide using COMSOL multiphysics - Nechibvute, Action; Mudzingwa, Courage (2016)
In this paper we investigate by simulation the dependence of the numerical aperture, normalized frequency and power propagating in the fibre, on the refractive index difference between the cladding and the core. The main purpose of the presented numerical modelling results is developing a simple method of investigating performance and optimization of single mode fibres. The numerical studies presented in this paper rely on solving the equations of electromagnetic waves propagation into optical fibres by using the finite element method technique (FEM) in COMSOL Multiphysics® .